Medical bookplate collection in Lithuanian Library of Medicine (Journal of EAHIL, 2015)
This paper is a short history of the medical bookplate collection in the Lithuanian Library of Medicine (LLM). TheÂ first LLM’s exhibition of bookplate on medical theme was held in 1994. It was an international exhibition-competitionÂ dedicated to the 50th anniversary of the Library. 39 authors from 16 countries participated, exhibition catalogueÂ “Lithuanian Medicine” was issued. Ten years later the second exhibition was dedicated to the 60th anniversary of theÂ LLM. In November 2014 the third medical bookplate exhibition was opened and an exhibition catalogue “LithuanianÂ Medicine. 2014” was issued. LLM now has a nice medical bookplate collection, which contains approximately 600Â pieces. Collection includes works from more than 100 Lithuanian and 16 foreign authors. The article aim is toÂ introduce the collection and encourage others to share their experience of collection-forming.